FA07.06: PERSISTENT DYSPHAGIA IS A RARE PROBLEM AFTER LAPAROSCOPIC NISSEN FUNDOPLICATION. (14th September 2018) - Nikolic, Milena; Schwameis, Katrin; Semmler, Georg; Asari, Reza; Semmler, Lorenz; Steindl, Ariane; Mosleh, Berta; Schoppmann, Sebastian
Abstract: Background: Although around 30% of patients with gastroesophageal-reflux disease (GERD) are insufficiently treated with medical therapy, only 1% opt for surgical therapy. One of the reasons behind this multifactorial phenomenon is the described adverse effect of long term dysphagia or gastric bloating syndrome after surgical treatment. Aim of this study was to evaluate the most common side effects associated with anti-reflux surgery, as well as long term outcomes in a large cohort of highly surgically standardized patients after laparoscopic Nissen fundoplication (LNF). Methods: Out of a prospective patients database including all patients that underwent anti-reflux surgery between 01/2003 and 01/2017 at our institution, 350 consecutive patients after highly standardized LF were included in this study. A standardized interview was performed by one physician assessing postoperative gastrointestinal symptoms, proton pump inhibitor intake (PPI), GERD-Health-related-Quality-of-Life (GERD-HRQL), Alimentary Satisfaction (AS), and patients overall satisfaction. Results: After a median follow-up of 4 years, persistent dysphagia (PD) after LNF was observed in 8 (2%) patients, while postoperative gas-bloat syndrome in 45 (12.7%) cases. Endoscopic dilatation was needed in 7 (2%) patients due to dysphagia, and 19 (5%) patients underwent revision surgery due to recurrence of GERD. The postoperative GERD-HRQL total score was significantly reduced (2 (IQR, 0–4.3) vs. 19 (IQR, 17–32); P < 0.000) and the median alimentary satisfaction (AS) was 9/10. Heartburn relief was achieved in 83% of patients. Eighty-three percent of patients were free of PPI intake after follow up, whereas 4% of the patients reported irregular PPI-use. Conclusion: LNF is a safe and effective surgical procedure with low postoperative morbidity rates and efficient GERD-related symptom relief. PD does not represent a relevant clinical issue when LNF is performed in a surgical standardized way. These results should be the benchmark to which long-term outcomes of new surgical anti-reflux procedures are compared. Disclosure: All authors have declared no conflicts of interest.